Nifedipine-sensitive blood pressure component in hypertensive models characterized by high activity of either sympathetic nervous system or renin-angiotensin system - Zicha, J; Dobešová, Z; Behuliak, M; Pintérová, M; Kuneš, J; Vaněčková, I (Physiological research, 2014)
High blood pressure (BP) of spontaneously hypertensive rats (SHR) is maintained by enhanced activity of sympathetic nervous system (SNS), whereas that of Ren-2 transgenic rats (Ren-2 TGR) by increased activity of renin-angiotensin system (RAS). However, both types of hypertension are effectively attenuated by chronic blockade of L-type voltage-dependent calcium channel (L-VDCC). The aim of our study was to evaluate whether the magnitude of BP response elicited by acute nifedipine administration is proportional to the alterations of particular vasoactive systems (SNS, RAS, NO) known to modulate L-VDCC activity. We therefore studied these relationships not only in SHR, in which mean arterial pressure was modified in a wide range of 100-210 mm Hg by chronic antihypertensive treatment (captopril or hydralazine) or its withdrawal, but also in rats with augmented RAS activity such as homozygous Ren-2 TGR, pertussis toxin-treated SHR or L-NAME-treated SHR. In all studied groups the magnitude of BP response to nifedipine was proportional to actual BP level and it closely correlated with BP changes induced by acute combined blockade of RAS and SNS. BP response to nifedipine is also closely related to the degree of relative NO deficiency. This was true for both SNS- and RAS-dependent forms of genetic hypertension, suggesting common mechanisms responsible for enhanced L-VDCC opening and/or their upregulation in hypertensive animals. In conclusions, BP response to nifedipine is proportional to the vasoconstrictor activity exerted by both SNS and RAS, indicating a key importance of these two pressor systems for actual L-VDCC opening necessary for BP maintenance.
Keywords: modely nemocí na zvířatech; potkani transgenní; potkani inbrední WKY; Male; hypertenze; sympatický nervový systém; náhodné rozdělení; nifedipin; potkani inbrední SHR; mužské pohlaví; blokátory kalciových kanálů; Hypertension; Rats, Transgenic; krysa rodu Rattus; Animals; Calcium Channel Blockers; Nifedipine; krevní tlak; Sympathetic Nervous System; renin-angiotensin systém; zvířata; Renin-Angiotensin System; Rats; Blood Pressure; Disease Models, Animal; Random Allocation; Rats, Inbred SHR; Rats, Inbred WKY